Companion animals and well-being in palliative care nursing: a literature review - MacDonald, Julie M.; Barrett, David (Journal of clinical nursing, 2016)
Aims and objectives To evaluate and critique current knowledge regarding the role of animals in palliative care. To explore the impact that animals may have on the well-being of individuals and to identify gaps in the evidence base. Background There is recognition that having a companion animal will affect patient experience. Similarly, there has been some previous exploration on the use of specific animal assisted therapies for patients with different healthcare needs. Design A literature review was conducted to identify published and unpublished research about companion animals or animal-assisted therapy in palliative and/or end-of-life care. The primary objective was to explore the impact of animals on well-being at the end of life. Methods A search for literature was carried out using a variety of databases and different combinations of search terms linked to animals in palliative care. Included works were critically appraised and thematically analysed. Results A limited range of literature was identified. From the small number of studies included in the review (n = 4), it appears that there is some evidence of animals (either companion animals or those used specifically to enhance care) having a positive impact on the patient experience. Conclusion This study suggests that animals play a large part in the lives of people receiving palliative care. Using animals to support care may also offer some benefits to the patient experience. However, there appears to be a dearth of high-quality literature in this area. More research is therefore required. Relevance to clinical practice Nurses providing palliative care need to be aware of the part that a companion animal may play in the life of patients. There may also be the opportunity for nurses in some settings to integrate animal therapy into their provision of palliative care.
Keywords: Complementary therapies; End-of-life care; Nursing care; Palliative care